2017
DOI: 10.36876/smjo.1050
|View full text |Cite
|
Sign up to set email alerts
|

Muscle and Osteoarthritis Joint Status: Current Research Highlights and Their Implications

Abstract: Osteoarthritis, a disabling disease, commonly believed to originate in the articular cartilage of freely moving joints, affects the entire joint, including muscle. This brief highlights the current research being published in this respect, an area of research that is not well documented when compared to related studies of cell biology, tissue engineering, and molecular in vitro studies, among others. To this end, to update a prior analysis, PUBMED, and Web of Science indices were searched for information speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 73 publications
(118 reference statements)
0
6
0
Order By: Relevance
“…Similarly, why this does not occur in all cases should be examined, especially since excess exercise could worsen the state of joint effusion and inflammation plus muscle inhibition that worsen the ability to protect the joint from impact. As was concluded in 2017 [21], the current literature base, while expanding and promising, remains too diverse and non-compelling to definitively drive clear evidence based guidance in our view.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, why this does not occur in all cases should be examined, especially since excess exercise could worsen the state of joint effusion and inflammation plus muscle inhibition that worsen the ability to protect the joint from impact. As was concluded in 2017 [21], the current literature base, while expanding and promising, remains too diverse and non-compelling to definitively drive clear evidence based guidance in our view.…”
Section: Discussionmentioning
confidence: 95%
“…This year was specifically selected for study in light of possible changes to the nature of research approaches and patient presentations in the post COVID realm. Previous data are included as indicated in this report to provide context for this ensuing discussion, and readers are directly to past reviews that can be examined separately to highlight the level of interest, scope, and findings that undergird this realm of inquiry [19][20][21][22][23][24]. Excluded were balance studies, ligament and meniscus studies, exercise or physical intervention studies, post-surgical studies, lab studies, and mixed studies that did not focus solely on the knee extensors in the context of knee osteoarthritis.…”
Section: Methodsmentioning
confidence: 99%
“…Sit-to-stand involve a very dynamic movement that requires broad joint movement of the lower extremity and trunk, which is typically repeated in activities of daily living. It is the most frequently used functional movement when the flexion of knee in closed chain changes to extension, and such posture change applies heavy load on the lower extremity (Hodge et al, 1989;Marks, 2017). According to previous studies, since the knee extensor is activated by a higher rate than other lower extremity muscles during sit-to-stand, the vastus medialis and rectus femoris are activated, especially before knee extension begins, while after knee extension begins, the hamstring and hip muscles are activated (Schenkman et al, 1996;Hughes et al, 1996;Anan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Sit-to-stand, which involve switching from knee flexion in a closed chain of the lower extremity to knee extension, is the most frequently used functional movement in ordinary life (Marks, 2017). It is reported that, when sit-to-stand is performed, the vastus medialis and rectus femoris are activated before extension of the knee begins, and the hamstring and hip muscles are activated after extension of the knee begins (Anan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to those studies depicted in Table 1, adding to the diversity of information retrieved is the fact that, as with prior research [53], almost all additional studies reviewed employed differing osteoarthritis samples, research questions, assessment approaches, and durations, and even if a similar variable or idea was examined, basically no two conclusions were alike. Indeed, some reported associations between reduced rates of torque development and osteoarthritis features, while others noted a propensity for fat cells in muscle to increase the risk for osteoarthritis [see Figure 1].…”
Section: Additionalmentioning
confidence: 99%